The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.4025/actascianimsci.v40i1.39077
|View full text |Cite
|
Sign up to set email alerts
|

<b>Replacing fish meal by mealworm (<i>Tenebrio molitor</i>) on the growth performance and immunologic responses of white shrimp (<i>Litopenaeus vannamei</i>)

Abstract: The objective of this study was to determine the effect of replacing FM with mealworm (Tenebrio molitor) on the growth performance and immunologic responses of white shrimp. In addition, the toxicity of such replacement to white shrimp was measured. Mealworm was incorporated to partially or totally replace fish meal in diets for white shrimp. Experimental groups of shrimp with an average initial body weight of 2.39 ± 0.49 g were fed each of 4 isonitrogeneous diets formulated to include 0, 25, 50 and 100% (cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
29
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 12 publications
(15 reference statements)
6
29
1
Order By: Relevance
“…Choi et al (2018) reported significant improvements in the THC when insect meal fed shrimp (50% FM replacement) were challenged with the pathogen that causes white spot syndrome virus (WSSV) [21]. Similarly, in the present study, in pre-challenged shrimps, THC showed an improvement that positively correlated with the YM dietary levels.…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…Choi et al (2018) reported significant improvements in the THC when insect meal fed shrimp (50% FM replacement) were challenged with the pathogen that causes white spot syndrome virus (WSSV) [21]. Similarly, in the present study, in pre-challenged shrimps, THC showed an improvement that positively correlated with the YM dietary levels.…”
Section: Discussionsupporting
confidence: 72%
“…Choi et al (2018) reported similar results when replacing FM with a full-fat T.molitor meal in Pacific white shrimp diet. The authors suggested that an insect meal improves growth performance of the shrimp because it contains essential amino acids [21].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations